An improved mass transfer model for film condensation numerical simulation. (March 2023) - Bai, Wandong; Chen, Wei; Li, Mingfei; Rao, Mumin; Chyu, Minking K.
Highlights: The manuscript presents an improved mass transfer model to solve the problem of empirical coefficient uncertainty in the Lee phase change model for two-phase multiphase flow simulation. The highlights of the study are summarized as follows: An improved mass transfer model was developed for film condensation simulation. Interfacial temperature difference was introduced to regulate interfacial behavior. The developed model was evaluated and proved its accuracy. Condensation characteristics under various operating conditions were investigated. Abstract: Numerical simulation for condensation applications is restricted by phase change modeling. The mass transfer relaxation coefficient in the Lee model is commonly an empirical constant, which makes simulation work inefficient due to the trouble in coefficient determination. An improved model has been developed to resolve this weakness by introducing a controllable parameter of interfacial temperature difference. The model was carefully validated in good agreement with the results from Nusselt's theory, empirical correlation, and experimental study. The parameter was demonstrated to play a key role that affects interfacial behavior significantly. The condensation heat transfer tended to be accurate when the parameter was reduced to a certain degree. Further, the developed model was used to investigate condensation heat transfer for inclined plates, microgravity environments, and flowing vapor. The model was capable of capturing heat transfer characteristics for these condensation applications. Despite the simplicity of the model, it is believed that this study will support future research and application in targeting the field of multiphase flow in engineering.